Antidepressant effects of Aloe vera hydroalcoholic extract - Salehi, Bahareh; Biazar, Esmaeil; Hadipour Jahromi, Mahsa; Akbari Romani, Hanie (Archives of Advances in Biosciences, 2011)
The antidepressant effects of aloe vera hydro alcoholic extract at different concentrations were compared with the fluoxetine-treated and the control groups of mice using forced-swimming, FST and open box, OFT tests. The mice were evaluated in five groups (control, taking aloe vera at the dosage levels of 150 mg/kg, 300 mg/kg, and 450 mg/kg, and finally fluoxetine at a dose of 10 mg/kg) by the FST and OFT tests on 1st, 7th, and 14th days. The results of the OFT test showed no significant differences between these five groups. The results of FST test indicate the antidepressant effects of aloe vera even at low doses and it was found that the effect of fluoxetine at a dose of 10 mg/kg was equivalent to the effect of aloe vera at a dose of 150 mg/kg for the reduction in immobility time in mice in FST test. According to the results obtained from FST test, the antidepressant effects on mice treated with the 450 mg/kg dose of aloe vera showed better recovery as compared with other groups on 1st, 7th, and 14th days. With regard to the experiments performed at different times, all the evidence pointed to the conclusion that the antidepressant effect of aloe vera was more than the control group. Based on the results of the OFT and FST tests, aloe vera extract at different doses, has favorable antidepressant effects on mice as compared to the fluoxetine-treated and the control groups and<span style="font-size: 11pt; color: black; font-family: BZar; mso-bidi-language: FA; mso-ascii-font-family: BZar; mso-bidi-font-family: 'B Lotus'; mso-fareast-font-family: 'Times New Roman'; mso-themecolor: text1;"> the better effects were seen by increasing the dose and duration of drug use.